US Medical Schools' Awareness of Their Students Who Smoke, Cessation Programs Available, and the Potential Impact on Residency Match. Issue 1 (27th October 2016) - Chidiac, Joseph E; Mohamed, Ahmed; Krishnamoorthy, Madhumitha; Mahmoud, Karim; Al-Darwash, Yassir; Rajasekaranrathnakumar, Geethapriya; Palla, Mohan; Levine, Diane L
Abstract: Introduction: Hospital systems are adopting strict nicotine-free policies excluding hiring individuals who smoke, including residents for graduate medical training. This study was conducted to (1) determine medical schools' awareness of these policies, (2) awareness of their students' smoking behaviors, and (3) the smoking cessation programs that they provide. Methods: A survey was developed to learn about the smoking policies of medical schools in the United States: how school leadership estimates smoking prevalence among their students, what those estimates are, and what programs are in place to help students quit smoking. Questions were asked about awareness of policies restricting hiring smokers including applicants for residency training. Opinions were solicited on including smoking status in medical school applications. The online survey was sent to the Deans of student affairs at US medical schools. Results: Of the 160 schools invited to participate, 84 (53%) responded. Most medical schools (92%) are smoke-free and 97% have policies specifically prohibiting tobacco use on campus. Estimates of student smoking prevalence varied from 0% to 34% with a mean of 6%. More than half of schools (52%) had no smoking-cessation programs to help students. Despite recent trends in policies that prohibit smokers from being hired into residency training programs, only 22% were aware of such policies. There were no statistically significant differences by school size, location or category (allopathic, osteopathic, public or private). Conclusions: Medical schools need to be aware of new hiring policies and take steps to identify and help their students quit smoking to ensure all students can secure residency training upon graduation. Implications: This study draws attention to recent policies that preclude hiring medical students who smoke for post graduate (residency) training. Our study demonstrates a lack of appreciation of these policies by medical school administration in the United States. Our study also provides information on smoking rates of medical students, as well as the prevalence and use of smoking cessation programs available through schools of medicine. The study supports the need for medical schools to identify and aid students who smoke to become nicotine-free so that they can secure residency training positions.